Detours: Binary Interception of Win32 Functions - Hunt, Galen; Brubacher, Doug (Third USENIX Windows NT Symposium, 1999)
Innovative systems research hinges on the ability to easily instrument and extend existing operating system and application functionality. With access to appropriate source code, it is often trivial to insert new instrumentation or extensions by rebuilding the OS or application. However, in today's world of commercial software, researchers seldom have access to all relevant source code. We present Detours, a library for instrumenting arbitrary Win32 functions on x86 machines. Detours intercepts Win32 functions by re-writing target function images. The Detours package also contains utilities to attach arbitrary DLLs and data segments (called payloads) to any Win32 binary. While prior researchers have used binary rewriting to insert debugging and profiling instrumentation, to our knowledge, Detours is the first package on any platform to logically preserve the un-instrumented target function (callable through a trampoline) as a subroutine for use by the instrumentation. Our unique trampoline design is crucial for extending existing binary software. We describe our experiences using Detours to create an automatic distributed partitioning system, to instrument and analyze the DCOM protocol stack, and to create a thunking layer for a COM-based OS API. Micro-benchmarks demonstrate the efficiency of the Detours library.